A NEW SPECIES UNDER MONOBASIC GENUS CHLOROLYCHNIS MEYRICK, ALONG WITH CORRECTION OF ITS FAMILY STATUS (LEPIDOPTERA : LECITHOCERIDAE) - WALIA, V.K.; WADHAWAN, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
A new species Chlorolychnis faridabadensis, named after the type locality Faridabad in the state of Haryana is described in detail. Relevant illustrations of wing venation and male genitalia supplement the description of the first record from North India under monobasic genus Chlorolychnis Meyrick. In the light of observed characteristic attributes of male genitalia, the aforementioned genus is shifted from family Gelechiidae to Lecithoceridae.